Clinical Outcomes Following Primary Anterior Cruciate Ligament Reconstruction with Hamstring Autograft versus Planned Hybrid Graft - Kraeutler, Matthew J.; Kim, Seong H.; Brown, Colin C.; Houck, Darby A.; Domby, Brian C.; Reynolds, Kirk A.; McCarty, Eric C. (The Journal of Knee Surgery, 2018)
Few studies have compared outcomes between autografts versus hybrid grafts (combination of autograft and allograft) for anterior cruciate ligament reconstruction (ACLR). The purpose of this study was to compare revision rate and patient-reported outcomes following primary ACLR with a hamstring autograft versus a preoperatively planned hybrid autograft-allograft. At a minimum 2-year follow-up, patients who had undergone primary ACLR with a double-stranded semitendinosus and gracilis hamstring autograft (A) or a planned hybrid (H) graft (single-strand semitendinosus with nonirradiated peroneus longus or tibialis posterior allograft) were contacted to fill out a survey containing the Knee Injury and Osteoarthritis Outcome Score (KOOS), Subjective International Knee Documentation Committee (IKDC) score, Single Assessment Numeric Evaluation (SANE), 12-Item Short-Form Health Survey (SF-12), and visual analog scale (VAS) for activity level prior to injury and at follow-up. From this collection of patients, a matched-pair comparison was made between groups, with patients matched by gender, age at the time of surgery, and follow-up time. Revision rate at follow-up was 8.4 and 2.4% in the A and H groups, respectively (p = 0.073). A total of 148 surveys were completed (83 A, 65 H), from which 36 matched pairs were formed. Within the matched pairs, average age at surgery did not differ significantly between groups (A: 35.7 years, H: 36.0 years, p = 0.23). Time to follow-up was 4.3 and 3.7 years in the A and H groups, respectively. Patients with a hybrid graft had significantly higher KOOS Quality of Life subscores (A 69.6, H 79.2, p = 0.028), subjective IKDC scores (A 72.6, H 79.7, p = 0.031), and SANE scores (A 83.2, H 91.4, p = 0.015) at follow-up. Otherwise, no significant differences were found in patient-reported outcome scores between groups. A preoperatively planned hybrid graft, with use of a fresh-frozen, nonirradiated allograft, should be considered as a viable alternative for primary ACLR in older patients.
Keywords: anterior cruciate ligament reconstruction; hamstring autograft; hybrid graft; graft failure